2021
DOI: 10.1002/adom.202002023
|View full text |Cite
|
Sign up to set email alerts
|

Avalanche Effect and High External Quantum Efficiency in MgZnO/Au/ZnO Sandwich Structure Photodetector

Abstract: MSM structure is widely applied to PD owing to its relatively simple preparation methods, short response time, and more effective light collecting area. However, MSM PD poses significant challenges that are mainly related to the external quantum efficiency (EQE) and weak light detection, owing to the optical loss of incident light by electrode shielding and the necessity of applying a bias voltage for device operation. To increase the EQE of PDs and probe weak signals, extensive research efforts have been devo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Preliminary analysis suggests that the external quantum efficiencies (EQEs) of both PDs exceeds 100%, which may be attributed to the strong depolarization electric field within the ferroelectric PZT thin film. Briefly, the strong depolarization electric field effectively separates the photogenerated charge carriers, and it may further produce additional charge carriers simultaneously via the typical impact ionization process. However, the mechanisms of such interesting results need to be explored in depth in the future. It is worth noting that the photodetection performances of our PDs are better than related works reported before (Table ), which can be attributed to the high optical transparency of the top Au electrode, efficient optical absorption, and improved ferroelectric properties of the PZT thin film.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary analysis suggests that the external quantum efficiencies (EQEs) of both PDs exceeds 100%, which may be attributed to the strong depolarization electric field within the ferroelectric PZT thin film. Briefly, the strong depolarization electric field effectively separates the photogenerated charge carriers, and it may further produce additional charge carriers simultaneously via the typical impact ionization process. However, the mechanisms of such interesting results need to be explored in depth in the future. It is worth noting that the photodetection performances of our PDs are better than related works reported before (Table ), which can be attributed to the high optical transparency of the top Au electrode, efficient optical absorption, and improved ferroelectric properties of the PZT thin film.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, several studies have reported APD with EQE higher than 100% for UV detection. [ 37,39,40 ]…”
Section: Characterizationmentioning
confidence: 99%
“…The free carriers that pass through the Ga 2 O 3 /Se heterojunction would begin accelerating to high energy and generate more charge carriers by ionization collision. [18,[35][36][37] The electric field in the c-Se layer is calculated to be %1 Â 10 5 V cm À1 . This current increase is considered to be the onset of avalanche behavior.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the improvement of social needs and people’s lives, UV PDs have become important devices for human activities. UV PDs have been widely used in military fields and commercial, such as gas sensing, missile detection, flame sensing, UV guidance, fire detection, environmental monitoring, medical applications, and optical communications . The band gap of ZnO is 3.37 eV, and the corresponding absorption wavelength is in the UV band. , Therefore, it shows that ZnO is an exceedingly good UV PD material.…”
Section: Introductionmentioning
confidence: 99%